Assessment of the Impacts of Centipeda minima (L.) on Cell Viability, and Osteogenic Differentiation of Mesenchymal Stem Cell Spheroids - Hyun-Jin Lee; Kyung-Hwan Na; Md. Salah Uddin; Jun-Beom Park (Medicina, 2022)
Background and Objectives: Centipeda minima (L.) is a well-known and traditional pharmaceutical that has been utilized to treat different conditions controlling rhinitis, soothe pain, and decrease swelling. We assessed the impacts of Centipeda minima (L.) extricates (CMTs) on the osteogenic differentiation of cell spheroids made of human-bone-marrow-derived mesenchymal stem cells. Materials and Methods: Mesenchymal stem cells (MSCs) in spheroid 3D culture were generated and propagated in the presence of CMTs ranging from 0 to 1 μg/mL. Cell morphology was measured on Days 1, 3, 5, and 7. The quantitative cellular viability was evaluated on Days 1, 3, 5, and 7. Alkaline phosphatase activity assays were designed to measure the osteogenic differentiation of mesenchymal stem cell spheroids on Day 7. Alizarin Red S staining was performed to investigate the mineralization of cell spheroids on Days 7 and 14. Real-time polymerase chain reactions were used to measure the expression levels of RUNX2 and COL1A1 on Day 14. Western blot techniques were performed to identify the protein expression of Runt-related transcription factor 2 and type I collagen. Results: The control group’s mesenchymal stem cells displayed a spheroid shape. There was no noticeable change in morphology with the addition of CMTs at final concentrations of 0.001, 0.01, 0.1, and 1 μg/mL compared with the untreated (control) group. The application of CMTs did not induce a significant change in cell viability. The relative alkaline phosphatase activity values in the 0.001, 0.01, 0.1, and 1 μg/mL CMT groups were 114.4% ± 8.2%, 130.6% ± 25.3%, 87.8% ± 3.4%, and 92.1% ± 6.8%, respectively, considering a control of 100% (100.0% ± 17.9%). On Day 14, calcium deposits were clearly observed in each group. The relative values of Alizarin Red S staining in the 0.001, 0.01, 0.1, and 1 μg/mL CMT groups were 100.1% ± 8.9%, 105.9% ± 0.0%, 109.7% ± 19.1%, and 87.0% ± 40.9%, respectively, considering a control of 100% (100.0% ± 28.7%). The addition of CMT significantly increased RUNX2 expression in the 0.01 μg/mL group and COL1A1 in the 0.001 and 0.01 μg/mL groups. Normalization of protein expression showed that the addition of CMTs significantly increased type I collagen expression in the 0.001, 0.01, and 1 μg/mL groups. Conclusions: In conclusion, CMTs influence the osteogenic differentiation of bone-marrow-derived mesenchymal stem cells and the use of CMTs may positively influence the osteogenic differentiation of cell spheroids.